Does population aging affect economic growth in Malaysia? - Ismail, Normaz Wana; Abdul Rahman, Siti Wardah; Tengku Abdul Hamid, Tengku Aizan (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2015)
The purpose of this study is to examine the impact of aging on economic growth. The study used dynamic growth model and employed ARDL approach for the period of 1970 to 2013. Three proxies for aging are used namely fertility rate, life expectancy and old dependency ratio. However, only fertility rate detect to have a long run cointegration. The major findings of this study revealed that a reduction of fertility rate lead to higher economic growth. This implied that even though Malaysia will face aging society by 2020, the economic growth still stable and can increase by investing more on human capital.